2005
DOI: 10.1111/j.1742-4658.2005.04575.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the heparin‐binding domains of the interferon‐induced protein kinase, PKR

Abstract: PKR is an interferon‐induced serine‐threonine protein kinase that plays an important role in the mediation of the antiviral and antiproliferative actions of interferons. PKR is present at low basal levels in cells and its expression is induced at the transcriptional level by interferons. PKR's kinase activity stays latent until it binds to its activator. In the case of virally infected cells, double‐stranded (ds) RNA serves as PKR's activator. The dsRNA binds to PKR via two copies of an evolutionarily conserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…29 The full length K296R mutant binds and is phosphorylated by the wild-type enzyme, and has been widely used to study PKR autophosphorylation and dimerization. 1,11,17,19,20,21,25,26,30 Important for the NMR studies, this mutant can not autophoshorylate during bacterial expression, and therefore does not dimerize. 21,30 Limited proteolysis experiments on the full-length protein identified a domain coinciding with the product of caspase cleavage during apoptosis, D251-C551.…”
Section: Resultsmentioning
confidence: 99%
“…29 The full length K296R mutant binds and is phosphorylated by the wild-type enzyme, and has been widely used to study PKR autophosphorylation and dimerization. 1,11,17,19,20,21,25,26,30 Important for the NMR studies, this mutant can not autophoshorylate during bacterial expression, and therefore does not dimerize. 21,30 Limited proteolysis experiments on the full-length protein identified a domain coinciding with the product of caspase cleavage during apoptosis, D251-C551.…”
Section: Resultsmentioning
confidence: 99%
“…Despite these similarities, distinct differences in the 59-end requirements of ppp-ssRNA and dsRNA exist-requiring and not requiring a 59-triphosphate, respectively-suggesting potential mechanistic disparities between these two classes of activators. Indeed, ssRNA displays coarse structural similarity to a non-RNA activator of PKR, the polyanion heparin, which has been shown to bind basic residues near the active site in the kinase domain (Fasciano et al 2005a). To elucidate the mechanism of activation of PKR by ppp-ssRNA, we sought to elucidate the role, if any, of the dsRBD in such activation.…”
Section: Binding Of 59-triphosphate Rna and Heparin Requires The Dsrbdmentioning
confidence: 99%
“…Because ssRNA and heparin are both non-dsRNA polyanion activators, we thought that they might have similar mechanisms of activation. Heparin has been shown to bind clusters of basic amino acids at the entrance to the kinase active site that are nonoverlapping with the dsRBD, suggesting a primarily electrostatic as opposed to structure-based mechanism of activation (Fasciano et al 2005a). Furthermore, it has been shown that heparin can activate a truncated version of PKR that does not contain the dsRBD, although the extent of activation was strongly diminished relative to fulllength PKR (Patel et al 1994;George et al 1996;Fasciano et al 2005a).…”
Section: Binding Of 59-triphosphate Rna and Heparin Requires The Dsrbdmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently demonstrated that PKR can also be activated by relatively unstructured ssRNA transcripts if a 59-triphosphate is present, wherein the 59-triphosphate likely serves as a pathogen-associated molecular pattern (PAMP) (Nallagatla et al 2007). PKR can also be activated by non-RNA molecules including heparin, dextran sulfate, and poly-L-glutamate (Hovanessian and Galabru 1987;Fasciano et al 2005). Despite identification of these diverse PKR activators, a clear understanding of the RNA molecular patterns that affect PKR activation has not been achieved.…”
Section: Introductionmentioning
confidence: 99%